Optimizing Decision-Making in Soccer: Analyzing Visual Search Strategies Across Skill Levels - Shen Tai Chong (Ilmu Inovasi Nusantara, 2025)
This study examines the impact of visual search features on decision-making among soccer players, specifically analyzing the different search strategies employed based on athletes' skill levels. The research aims to understand how athletes at varying levels use visual cues to enhance decision-making during gameplay. To achieve this, a comprehensive review of relevant literature from domestic and international databases was conducted, selecting studies based on predefined inclusion criteria to extract data and analyze the visual characteristics of athletes across skill levels. The findings reveal that high-level athletes exhibit faster reaction times, are better at extracting critical information from key areas of interest, and that their psychological state influences reaction time. High-level athletes possess response templates for sports scenarios, leading to shorter gaze durations, fewer fixations, and quicker gaze transitions. These athletes also show a more extensive eye movement range, which allows for the collection of more information and, through long-term training, enhances the efficiency of their information-processing strategies. Consequently, high-level athletes demonstrate optimized visual search strategies compared to novice players, resulting in more accurate and rational decision-making during gameplay. The study recommends further developing visual training programs to support novice athletes in improving their information processing and decision-making capabilities, which could ultimately bridge the gap between skill levels and enhance performance